2021
DOI: 10.1080/1331677x.2021.1922089
|View full text |Cite
|
Sign up to set email alerts
|

Predicting financial market returns in the presence of health crisis: evidence from conventional and Islamic stock markets

Abstract: The purpose of this study is to examine the usability of the news about the COVID-19 outbreak as a predictor in financial markets. Index values of 11 different sectors in conventional and Islamic stock markets and the index values obtained from COVID-19 deaths, COVID-19 cases and health news were used for this purpose. News variables indices were calculated through Google search volume (G.S.V.) values obtained from Google trend. The daily data between 19 March 2020 and 27 July 2020 were used in the study for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
2
5
1
1
Order By: Relevance
“…The result of this study is also not in line with the study conducted by Tuna (2021). He showed that conventional, as well as Sharia stock markets in the period from 19 March 200 to 27 July 2020, were not efficient.…”
Section: Resultscontrasting
confidence: 88%
“…The result of this study is also not in line with the study conducted by Tuna (2021). He showed that conventional, as well as Sharia stock markets in the period from 19 March 200 to 27 July 2020, were not efficient.…”
Section: Resultscontrasting
confidence: 88%
“…PAI's impact is stronger in the stock-Ethereum comovements, positive in Canada, the US, France, Germany, and Italy, and negative in the UK stock markets. To a certain extent, the results imply that investor sentiment or fear of the uncertainties triggered by COVID-19 plays a role in their investment decisions, as earlier asserted by [21,33]. In addition, the results also imply that Bitcoin is an investment choice for institutional and high-worth investors who have the resources and reliable sources of information to make longer-term investment decisions.…”
Section: Seemingly Unrelated Regression (Sur)supporting
confidence: 54%
“…In a period of heightened market uncertainties, investors make irrational decisions driven by their appetite for risk-taking and loss aversion. Investors are not always rational in making decisions because they are social creatures whose judgment and behavior are influenced by their surroundings and social circles [25,33]. Herding, irrational judgments, and fear of future uncertainties result in excessive trading that causes market volatilities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve this problem, this chapter introduces the "value function" of the state in the MDP model. Reference [26]. Its function is mainly to evaluate the benefits brought by the current decision and the impact on the subsequent income acquisition trend, so as to quantitatively evaluate the potential benefits under each system state.…”
Section: Joint Optimization Problem Modeling Based On Markovmentioning
confidence: 99%